2016
DOI: 10.1111/hir.12151
|View full text |Cite
|
Sign up to set email alerts
|

Demonstrating the financial impact of clinical libraries: a systematic review

Abstract: Objective: The purpose of this review is to evaluate the tools used to measure the financial value of libraries in a clinical setting. Methods: Searches were carried out on ten databases for the years 2003-2013, with a final search before completion to identify any recent papers. Results: Eleven papers met the final inclusion criteria. There was no evidence of a single 'best practice', and many metrics used to measure financial impact of clinical libraries were developed on an ad hoc basis locally. The most co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 72 publications
1
17
0
Order By: Relevance
“…Measures of medical librarian value include time saved, value of resource collection, cost avoidance, and revenue generated from accepted grants [10]. One study found that utilizing librarianprovided services that directly related to patient care decreased the length of stay [11].…”
Section: Valuementioning
confidence: 99%
“…Measures of medical librarian value include time saved, value of resource collection, cost avoidance, and revenue generated from accepted grants [10]. One study found that utilizing librarianprovided services that directly related to patient care decreased the length of stay [11].…”
Section: Valuementioning
confidence: 99%
“…This issue is one of two halves, one focused on quantifying aspects of service provision 1,2 and the other focused on information seeking behaviour 3,4 …”
Section: In This Issuementioning
confidence: 99%
“…Madden et al . 's1 systematic review seeks to evaluate the tools used to explicitly measure the financial impact of clinical libraries. They note that the tools used are typically developed locally, are implicit in nature and lack robustness seeking to measure financial impact in terms of time saved and cost avoidance.…”
Section: In This Issuementioning
confidence: 99%
“…The review article by Madden et al . is timely as it focuses on demonstrating the financial value of libraries in a clinical setting.…”
mentioning
confidence: 99%
“…The review article by Madden et al 2 is timely as it focuses on demonstrating the financial value of libraries in a clinical setting. The authors conducted a systematic review to evaluate tools that are used to measure financial impact of clinical libraries.…”
mentioning
confidence: 99%